The relationship of lamins with epigenetic factors during aging - R. N. Mustafin; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции)
The key factor of genome instability during aging is transposon dysregulation. This may be due to senile changes in the expression of lamins, which epigenetically modulate transposons. Lamins directly physically interact with transposons. Epigenetic regulators such as SIRT7, BAF, and microRNA can also serve as intermediaries for their interactions. There is also an inverse regulation, since transposons are sources of miRNAs that affect lamins. We suggest that lamins can be attributed to epigenetic factors, since they are part of the NURD, interact with histone deacetylases and regulate gene expression without changing the nucleotide sequences. The role of lamins in the etiopathogenesis of premature aging syndromes may be associated with interactions with transposons. In various human cells, LINE1 is present in the heterochromatin domains of the genome associated with lamins, while SIRT7 facilitates the interaction of this retroelement with lamins. Both retroelements and the nuclear lamina play an important role in the antiviral response of organisms. This may be due to the role of lamins in protection from both viruses and transposons, since viruses and transposons are evolutionarily related. Transposable elements and lamins are secondary messengers of environmental stressors that can serve as triggers for aging and carcinogenesis. Transposons play a role in the development of cancer, while the microRNAs derived from them, participating in the etiopathogenesis of tumors, are important in human aging. Lamins have similar properties, since lamins are dysregulated in cancer, and microRNAs affecting them are involved in carcinogenesis. Changes in the expression of specific microRNAs were also revealed in laminopathies. Identification of the epigenetic mechanisms of interaction of lamins with transposons during aging can become the basis for the development of methods of life extension and targeted therapy of age-associated cancer.